Existing Scenario, Through Evaluation and SWOT Review of e-Health Services in Bangladesh - Halim, Kazi Shafiqul; Nargis, Fatema (Bangladesh Medical Journal, 2025)
In recent years, Bangladesh has made considerable progress in digitizing its healthcare system through the introduction of e-Health services. ese services leverage information and communication technology (ICT) to improve healthcare delivery, particularly in rural and underserved regions where access to medical professionals is limited. e Government of Bangladesh, in partnership with non-governmental organizations (NGOs) and private stakeholders, has initiated several programs including telemedicine services, mobile health (mHealth), electronic health records (EHRs), and digital health portals. Notable government-led initiatives include the deployment of telemedicine centers at Upazila Health Complexes, SMS-based health advisories, and the “Health Call Center” (16263), which o€ers 24/7 medical consultation. Additionally, private sector platforms like Doctorola, Maya, and Tonic have gained popularity for providing remote consultations, mental health support, and digital prescriptions. However, despite these promising developments, e-Health in Bangladesh is still in a transitional phase. Challenges such as low digital literacy, inadequate internet connectivity in rural areas, shortage of trained personnel, and lack of interoperability among systems have limited its full potential. Bangladesh Med J. 2024 May; 53(2): 31-33